Analysis of Drought Impacts and Adaptation Strategies Of Smallholder Crop Farmers In Southern Kaduna, NigeriaAnalysis of Drought Impacts and Adaptation Strategies Of Smallholder Crop Farmers In Southern Kaduna, Nigeria - Dare, Akinrinshola; Onwuegbunam, Donatus Obiajulu; Maikano, Samson; Bolaji, Olusegun William; Okechalu, Samson Owunebe (FUDMA Journal of Sciences, 2026)
This study examines drought impacts and adaptation strategies among smallholder crop farmers in Southern Kaduna, Nigeria. The region, a major producer of ginger, maize, sorghum, and soybean, has experienced increasingly erratic rainfall over the past decade. Data were collected from 400 farmers across four Local Government Areas (Zangon Kataf, Kachia, Jema’a, and Kagarko) using structured questionnaires, focus group discussions, and key informant interviews, alongside historical meteorological data (2014–2023) from the Nigerian Meteorological Agency. Results show severe drought spells significantly reduced crop yields: maize and ginger fell by 44% and 36%, sorghum and soybean by 31% and 28%. These losses pushed 67% of surveyed households below the poverty line during drought years, with estimated annual economic losses of ₦12.4 billion across the four LGAs. Farmers adopted various coping mechanisms, including altering planting dates (82%), using early-maturing varieties (78%), crop diversification (65%), mulching (58%), and soil and water conservation (45%). However, capital-intensive adaptations like irrigation remained low (35%) due to financial constraints and poor institutional support. Social networks and cooperatives (52%) played significant roles in facilitating adaptation. The study concludes that indigenous strategies are insufficient to buffer severe drought shocks. It recommends increased government investment in small-scale irrigation, improved access to climate-resilient seeds, timely weather information dissemination, crop insurance schemes, and strengthened farmer cooperatives to enhance resilience against climate change